Using Multiple Natural Enemies to Manage Sweetpotato Whiteflies (Hemiptera: Aleyrodidae) in Commercial Poinsettia (Malpighiales: Euphorbiaceae) Production. Issue 1 (27th April 2021) - Vafaie, Erfan K; Pemberton, H Brent; Gu, Mengmeng; Kerns, David; Eubanks, Micky D; Heinz, Kevin M
Abstract: In this case study, we investigate the efficacy and economics of using two natural enemies in an integrated pest management (IPM) program to manage sweetpotato whitefly, Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae), in commercial poinsettia ( Euphorbia pulcherrima Willd. ex Klotzsch) production. Two similar greenhouses at each of three different grower locations were designated as either the IPM or the conventional insecticide greenhouses in southeastern United States. In the IPM greenhouses, we released Eretmocerus eremicus (Rose & Zolnerowich) (Hymenoptera: Aphelinidae) weekly and Amblyseius swirskii (Athias-Henriot) (Acari: Phytoseiidae) every 4 wk, and selective insecticides were used to treat high whitefly densities as needed. In the conventional greenhouses, growers were autonomous in their insecticide application decisions. All whitefly stages were counted weekly on a maximum of 20 leaves per 50 randomly sampled poinsettias and 50 flagged (i.e., revisited) poinsettias in every greenhouse. Whitefly densities were consistently similar or higher in the IPM greenhouses compared to their conventionally managed counterparts for the duration of the trial. The cost of inputs and labor for whitefly management in the IPM greenhouses was between 0.57- and 3.0-fold the cost of conventional management. Our study supports that releasing E. eremicus and A. swirskii can reduce insecticide applications by 25–78% and may be considered a feasible strategy to manage B. tabaci in commercial poinsettia production in place of conventional insecticidal control in southeastern United States.